Transparency, Liberalization, and Banking Crisis - Mehrez, Gil; Kaufmann, Daniel (World Bank, Washington, DC, 2014)
The authors investigate how transparency affects the probability of a financial crisis. They construct a model in which banks cannot distinguish between aggregate shocks and government policy, on the one hand, and firm' quality, on the other. Banks may therefore overestimate firms' returns and increase credit above the level that would be optimal given the firms' returns. Once banks discover their large exposure, they are likely to roll over loans rather than declare their losses. This delays the crisis but increases its magnitude. The empirical evidence, based on data for 56 countries in 1977-97, supports this theoretical model. The authors find that lack of transparency increases the probability of a crisis following financial liberalization. This implies that countries should focus on increasing transparency of economic activity and government policy, as well as increasing transparency n the financial sector, particularly during a period of transition such as financial liberalization.